Fatigue, physical activity, physical functioning and quality of life in older adults with cancer - Luctkar-Flude, Marian (University of Ottawa (Canada), 2007)
Cancer is predominantly a disease affecting older persons. 43% of new cancer cases in Canada occur among those who are at least 70 years old, while 25% occur in those aged 60--69 years. Cancer fatigue is the most common symptom associated with cancer and its treatment, and is often the most distressing symptom reported by cancer patients. Cancer fatigue adversely affects physical activity levels, physical function, and quality of life. Physical function is essential to older adults in maintaining independence and associated quality of life which is often more important to older adults than cancer survival. Recent research studies suggest that physical activity may reduce fatigue, and maintain or improve physical function levels and quality of life in cancer patients during and following treatment. This thesis examines cancer fatigue and its relationship to physical activity, physical function, and quality of life in older adults with cancer. The results of a systematic review and the findings of a secondary analysis research study are presented. The systematic review provided evidence that physical activity may reduce fatigue in older cancer patients during and after cancer treatment and may help to maintain or improve physical function and quality of life in this population. Results of the secondary analysis indicated that cancer fatigue is prevalent and was the most frequently reported symptom at baseline, three months and six months post consultation for cancer treatment. Cancer fatigue was associated with lower levels of physical function and quality of life. Physical activity, a modifiable factor, was found to be significantly related to cancer fatigue at three months and six months, regardless of age, and was significantly related to physical function at six months.
Keywords: Gerontology.; Health Sciences, Nursing.